2016
DOI: 10.1016/j.scitotenv.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimising value from the soft re-use of brownfield sites

Abstract: Soft re-use of brownfields describes intended temporary or final re-uses of brownfield sites which are not based on built constructions or infrastructure (‘hard' re-use). Examples of soft re-uses include the creation of public green space. These are essentially uses where the soil is not sealed. Often the case for soft re-use of brownfields has not been easy to demonstrate in strictly financial terms. The purpose of this paper is to describe a value based approach to identify and optimise services provided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 44 publications
0
51
0
3
Order By: Relevance
“…One locality, Milwaukee County, showed higher commercial (31%), industrial (19%), and residential reuse (20%), as compared to the national United States Conference of Mayors (USCM) survey responses from 99 cities, which reported 25% commercial, 18% industrial, and 14% residential reuse [8,17,22]. Despite the USCM's lead in confronting climate change locally, there has been a dearth of attention to adaptation needs and natural hazard vulnerabilities to inform cleanup priorities, bolster resilience and add greenspaces to meet community needs [46][47][48][49][50][51][52][53]. As a community-driven process, creating the vision for a healthier environment with brownfields reused as spaces for skills development, training or settings to foster community, employment, and civic participation, can also strengthen attention to flood-risk vulnerability [23,[53][54][55][56]].…”
Section: Land Reusementioning
confidence: 99%
See 2 more Smart Citations
“…One locality, Milwaukee County, showed higher commercial (31%), industrial (19%), and residential reuse (20%), as compared to the national United States Conference of Mayors (USCM) survey responses from 99 cities, which reported 25% commercial, 18% industrial, and 14% residential reuse [8,17,22]. Despite the USCM's lead in confronting climate change locally, there has been a dearth of attention to adaptation needs and natural hazard vulnerabilities to inform cleanup priorities, bolster resilience and add greenspaces to meet community needs [46][47][48][49][50][51][52][53]. As a community-driven process, creating the vision for a healthier environment with brownfields reused as spaces for skills development, training or settings to foster community, employment, and civic participation, can also strengthen attention to flood-risk vulnerability [23,[53][54][55][56]].…”
Section: Land Reusementioning
confidence: 99%
“…It remains unclear how often practitioners use general vulnerability assessment or hazard planning tools in specific site or area-wide brownfield assessment and cleanup practices [34,44,51,52]. …”
Section: Conceptual Model Of Community Environmental Health Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have revealed that experts are more concerned about future brownfi eld redevelopment efforts than about the results and success of prior projects. Since restoration projects should create overall positive value (Bardos et al, 2016), their assessment should be considered from a broad perspective. Wedding and Crawford-Brown (2007) applied a system of 40 indicators of successful brownfi eld redevelopments covering the following areas: environment and health, fi nancial indicators, social and economic indicators, and liveability indicators.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Brownfields are also described as a territory that is affected by the previous use or the impact of the surrounding land and becomes unused or useless without further intervention [3]. Brownfield land provides a possibility of using free space and potential for additional urban development considering changes in the needs of the population [4]. Regeneration is the most commonly used way to exploit the potential of brownfields [5][6][7].…”
Section: Introductionmentioning
confidence: 99%